Menganalisis Perbandingan Pendidikan Kurikulum Dinegara Indonesia Dan Negara Finlandia - Aldo Aldo; Ismi Rahmiyati; Taufik Muhtarom (Journal Innovation In Education, 2024)
When viewed from educational issues. In particular, the Indonesian curriculum can be categorized as a country whose education curriculum is still low, when compared with countries that have advanced education systems. Coupled with evidence from reports from the Organization for Economic Cooperation and Development (OECD) conducting an international survey using a test called the Program for Assessment (PISA). The method used in this paper is a literature review because it compares education systems, especially the curriculum between Indonesia and Finland. The curriculum components in question are results and discussion. Data collection methods are related to the topic of this paper. Primary School Curriculum in Finland and Indonesia The 2014 Finnish National Core Curriculum (FNCC) is divided into two parts. The general part includes the importance of the local curriculum, the local curriculum process, the mission and general objectives of basic education, as well as evaluation. In the primary school curriculum, the parts that relating to subjects is divided into several levels (grade 1, grade 2, and grades 3 to 6). The Finnish curriculum is designed to provide standard content and serve as a guide for educational institutions. Subjects are adapted by local authorities to the needs of students, schools, and even parents can participate in editing the curriculum and its objectives.Education in Finland is based on an integrated curriculum system.The Indonesian curriculum also includes several core subjects such as language, religious education, citizenship education, social studies, mathematics, science, physical education and sports, skills and vocational, arts and culture, as well as local content.